A systematic review of the association between history of sexually transmitted infections and subsequent condom use in adolescents - Frédérique Tremblay; Yohann Courtemanche; Richard E. Bélanger; Anne-Marie Tu (BMC, 2024)
Abstract Sexually transmitted infections (STIs) are common among adolescents. According to the Health Belief Model, cues to action influence preventive behaviors. Cues to action can include health experiences such as being diagnosed with an STI. The impact of a history of STIs on subsequent condom use among adolescents remains largely unexamined, despite high rates of recurrence and their health impacts. This project aimed to systematically review the literature on the association between curable STIs and subsequent condom use among adolescents. The systematic review, reported following PRISMA guidelines, was conducted using the Joanna Briggs Institute method. Eligible studies, in the form of cohort studies, case-control studies, or cross-sectional studies, targeted adolescents aged 10 to 24, with or without a history of curable STIs; the outcome was subsequent condom use. MEDLINE (Ovid), Embase (Elsevier), and Web of Science were searched from January 2012 to December 2022 with the assistance of an information specialist. Two reviewers independently selected articles and extracted data. Risk of bias analysis was performed using ROBINS-E. The review explores results, with tables, based on population characteristics, exposure, and outcome, and addresses the influence of gender, ethnicity, and age. Of 3088 articles identified, seven studies were retained. Almost all the studies focused on African-American, Nigerian, or Rwandan adolescents, and several included only girls. Among girls, a history of STI increased subsequent condom use in combination with other contraceptive methods (n = 4). Among boys and older adolescents of both genders, a history of STI was associated with a decrease in condom use (n = 3). No study distinguished between different STIs. While all the studies (n = 7) presented a high risk of bias, six did not present a threat to conclusion validity. All the studies indicated that a history of STI could influence subsequent protective behaviors, possibly by acting as a cue to action, as posited by the Health Belief Model. This information enhances our understanding of factors leading to the adoption of preventive health measures among adolescents and could apply to other infectious experiences. Registration The protocol is registered in PROSPERO (CRD42023397443).